Comparative assessment of the role of state, third sector and combined intervention of state and third sector in intervening income inequalities through SHGS - V.J., Byra Reddy; C, Shashidhar; K.N, Veena (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2013)
Inequality reduction in general and income inequality reduction in particular has occupied huge efforts/resources of the state since independence in India.Given that more than 300 million people are under poverty line in India today and the sheer deprivation that they face, evaluation of inequality reduction methods in India assume greater significance.In the above context, the present paper is an attempt to understand the effectiveness of income inequality reduction methods by the state, third sector and the combined intervention of the state and third sector.For this purpose four villages in the Gulbarga district of Karnataka were chosen to assess the relative effectiveness of the interventions by state, third sector and the combined interventions of state and third sector. The results of the study show that, Combined intervention of the State and Third Sector on Income inequalities through SHGs is distinctly better in providing regular employment to employed people than other types of intervention.Combined intervention of State and Third Sector in Income inequalities is distinctly better both in empowering people with higher incomes and discouraging people from borrowing money from money lenders at very high interest rates.It could also be concluded that combined intervention of State and Third Sector provides better terms of borrowing than State intervention alone or Third Sector intervention alone.Earning and saving patters are much better in combined intervention of State and Third Sector than other interventions.